2015
DOI: 10.1101/023846
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A decision underlies phototaxis in an insect

Abstract: Like a moth into the flame-phototaxis is an iconic example for innate preferences. Such preferences probably reflect evolutionary adaptations to predictable situations and have traditionally been conceptualized as hardwired stimulus-response links. Perhaps for that reason, the century-old discovery of flexibility in Drosophila phototaxis has received little attention. Here, we report that across several different behavioural tests, light/dark preference tested in walking is dependent on various aspects of flig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 77 publications
4
17
0
Order By: Relevance
“…Alternatively, a non-adaptive (or maladaptive) explanation is that herbivore attraction to light is too strong to permit foraging on the higher quality plants in nearby shade habitats. We regard the constraint hypothesis as intriguing but implausible, because phototactic behavior can vary plastically and genetically both between and within species of drosophilids (Gorostiza et al 2016). The fact that it persists in S. nigrita suggests that there may be benefits to feeding in warm, sunny habitats at >3000 m in elevation that outweigh any advantages to feeding on the more palatable host plants in the shade.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, a non-adaptive (or maladaptive) explanation is that herbivore attraction to light is too strong to permit foraging on the higher quality plants in nearby shade habitats. We regard the constraint hypothesis as intriguing but implausible, because phototactic behavior can vary plastically and genetically both between and within species of drosophilids (Gorostiza et al 2016). The fact that it persists in S. nigrita suggests that there may be benefits to feeding in warm, sunny habitats at >3000 m in elevation that outweigh any advantages to feeding on the more palatable host plants in the shade.…”
Section: Discussionmentioning
confidence: 96%
“…Supporting this notion, a recent study found that male flies frequently inflicted wing damage in aggressive bouts 37 . The increases in sleep we observe when flight is impaired, could thus be viewed as an adaptive response, enabling flies to modify their behavioural repertoire to meet new challenges 40 . Indeed, sleep has been proposed to serve as a state of 'adaptive inactivity'.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we evaluated a number of genetic manipulations that impair flight. Expressing the cell death activator reaper (UAS-rpr) in the wing disc, or mutations in wingless (wg), protein kinase c (pkc), and the commonly used CyO marker, all impair flight 40,41 and increase sleep (Extended Data Fig. 8, a-e).…”
Section: Disrupting Wings Increases Sleepmentioning
confidence: 99%
“…Finally, the avoidance of specific DRA medulla layers by large octopaminergic neurons suggests that neuromodulation may affect differently those visual circuits computing different visual modalities. Opposing effects of both octopamine and dopamine on visual behavior have previously been demonstrated (Gorostiza, Colomb et al 2016), and it remains to be seen how these neuromodulators affect navigation behaviors by modulating the underlying circuitry.…”
Section: Discussionmentioning
confidence: 99%